2021
DOI: 10.2903/j.efsa.2021.6576
|View full text |Cite
|
Sign up to set email alerts
|

The use of alkaline phosphatase and possible alternative testing to verify pasteurisation of raw milk, colostrum, dairy and colostrum‐based products

Abstract: Pasteurisation of raw milk, colostrum, dairy or colostrum-based products must be achieved using at least 72°C for 15 s, at least 63°C for 30 min or any equivalent combination, such that the alkaline phosphatase (ALP) test immediately after such treatment gives a negative result. For cows' milk, a negative result is when the measured activity is ≤ 350 milliunits of enzyme activity per litre (mU/L) using the ISO standard 11816-1. The use and limitations of an ALP test and possible alternative methods for verifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 121 publications
0
17
0
Order By: Relevance
“…A variability of ALP values was detected in Pecorino Siciliano cheese samples, particularly those produced with pasteurized milk. Several samples presented ALP values higher than 10 mU/g, a threshold reported by other authors [ 6 , 9 , 10 ]. These values discriminated against cheese produced with raw or pasteurized milk.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…A variability of ALP values was detected in Pecorino Siciliano cheese samples, particularly those produced with pasteurized milk. Several samples presented ALP values higher than 10 mU/g, a threshold reported by other authors [ 6 , 9 , 10 ]. These values discriminated against cheese produced with raw or pasteurized milk.…”
Section: Resultsmentioning
confidence: 49%
“…Several studies reported that cheese size impacts the residual activity of ALP and its zonal distribution [ 6 , 7 , 8 , 9 , 10 ]. Additionally, several authors agree that the temperature at which the curd is heated, and the size of the cheese wheel, are the main parameters that influence residual ALP activity in cheese [ 6 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations